Clay mineralogy of Brazilian oxisols with shrinkage properties - de Almeida J.A.* (2017)
© 2017, Revista Brasileira de Ciencia do Solo. All Rights Reserved.Shrinkage capacity (caráter retrátil in Portuguese) is a new diagnostic characteristic recently introduced in the Brazilian System of Soil Classification (SiBCS) to indicate shrink and swell properties observed in subtropical soils from highland plateaus in southern Brazil, specifically in Oxisols with brown colors. In soils located in road cuts exposed to drying for some weeks, strong shrinkage of soil volume is observed in these soils, resulting in the formation of pronounced vertical cracks and large and very large prismatic structures, which crumble in blocks when handled. We hypothesize that such properties are related to their clay mineralogy, although there are no conclusive studies about this, the motive for the present study. Samples of the A and B horizons from six Oxisols with expansive capacity from the states of Santa Catarina and Rio Grande do Sul were analyzed. One Rhodic Hapludox, from the state of Paraná, without expansive capacity, was used for comparison. All the soils are very clayey, originated from basalt, and have similar iron oxide content. For identification of clay mineralogy, X-ray diffraction techniques were employed, together with the use of NEWMOD® software to investigate and describe the interstratified minerals. The results showed that most expansive soils have a similar mineralogical composition, with kaolinite, interstratified kaolinite-smectite (K-S), and hydroxy-Al interlayered smectites (HIS), unlike the non-expansive Rhodic Hapludox, which exhibited kaolinite with significant amounts of gibbsite and low amount of interstratified K-S. According to the mineralogical assemblage identified in the expansive soils, we can affirm that the mechanism of smectite expansion and contraction is related to the shrinkage capacity of the soil, considering that the level of hydroxy-Al intercalation is low. In addition, these mechanisms also are related to the presence of quasicrystals and domains that control the water dynamic in the smectites, contributing to shrinkage capacity.